ANALISIS SWOT DALAM MENENTUKAN STRATEGI PEMASARAN KOSMETIK WARDAH DI KOTA BENGKULU - Herlin Herlin; Yesi Noti Anggraini; Rina Trisna Yanti (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2020)
ABSTRACTÂ The purpose of this research is to find out Wardah cosmetic product marketing strategy in Eljhon 2 Bengkulu. The analytical method used in this study is SWOT analysis (Strength, Weaknesses, Opportunities and Threats), with a total sample of 33 respondentsÂ Based on the results of the SWOT analysis using IFAS and EFAS analysis, it is located in the coordinates of the score (20.31: 1.16) and is in quadrant 1 with greater strength and opportunity than weaknesses and threats which support aggressive strategies, where strengths (strengths) worth 28.62 weaknesses worth 18.31 opportunities worth 17.27 and threats valued at 16.11. Quadrant 1, this is a very profitable position so that it can take full advantage of the company's strengths and opportunities.